(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The theory - the opinion of a lot of thinkers contemporary - important theories philosophical, social and which established to enter the era of modernity and beyond, may be a cash German philosopher Kant cornerstone in Renaissance European according to this theory, so try this search with a stamp philosophical and social that highlights the origin of the emergence of these critical theory since the beginning the first to Renaissance, as he tries to that keeps track of their development historical and philosophical and social conditions, political and the surrounding, and what is the position of some of the philosophers of these critical theory. However, the question, which can ask here, is a form of the following: is the critical theory in turn, social, political and in the community, and do have contributed to change the desired which seeks to in the community. The basis of this question it should we have to trace the process of its development historical, and to identify the most important views of the philosophers, which they told them